Effect of plasma on the radio-technical characteristics of the Uragan-2M torsatron matching RF systems - Korovin, V.B.; Filippov, V.V.; Kozulya, M.M.; Kramskoy, E.D.; Lozin, A.V. (Вопросы атомной науки и техники, 2014)
There were carried out qualitative studies of the effect of plasma parameters during the RF disharge wall conditioning in a helium atmosphere on the quality factor of the antenna oscillating circuit at Uragan-2M torsatron. The quality factor is determined from the ratio of the electric current in the circuit to the feed current. The dependence of the quality factor of the toroidal steady magnetic field as well as on the helical field is analyzed. The dependence on the helical field is much stronger; with its increase the quality factor increases that is accompanied with reduction of the antenna load. Also, the ratio of idling current in the antenna (when the plasma even less) to the current in the antenna is measured during the discharge. The dependence of this parameter on the toroidal magnetic field and the neutral gas pressure is studied. Проведены качественные исследования влияния плазмы в режиме ВЧ-чистки в атмосфере гелия на добротность антенного колебательного контура в торсатроне Ураган-2М. Добротность определялась из отношенния тока в контуре к току подводящего фидера Q=Ik/If. Проанализирована зависимость добротности как от тороидального поля, так и от винтового. Зависимость от винтового поля значительно сильнее, с его ростом добротность увеличивается, что соответствует снижению нагрузки антенны. Также измерялся параметр Iaxx/IaL, т.е. отношение тока в антенне в момент холостого хода генератора (когда плазмы еще нет) к току в антенне в момент разряда. Приведены зависимости этого параметра от тороидального поля и от давления. Проведені якісні дослідження впливу плазми в режимі ВЧ-чистки в атмосфері гелію на добротність антенного коливального контуру в торсатроні Ураган-2М. Добротність визначалась з відношення струму в контурі до струму підвідного фідера Q=Ik / If. Показана залежність добротності як від тороїдального, так і від гвинтового полів. Залежність від гвинтового поля значно сильніше, з ростом поля добротність збільшується, що відповідає зниженню навантаження антени. Вимірювався також параметр Iaxx / IaL, тобто відношення струму в антені в момент холостого ходу генератора (коли плазми ще немає) до струму в антені в момент розряду. Виявлено також залежності цього параметру від тороїдального поля та від тиску.